Exploring Research Trends and Future Works of Process-oriented Guided Inquiry Learning in Organic Chemistry: A Bibliometric Study - Hurrahman, Mifta; Atun, Sri; Erlina, Erlina; Sogen, Jasintah Tagan; Aisyah, Siti (Jurnal Pendidikan Matematika dan Sains, 2025)
This study aimed to investigate research trends and future works concerning the implementation of the Process Oriented Guided Inquiry Learning (POGIL) approach in organic chemistry learning. Employing the PRISMA protocol for systematic literature review and bibliometric analysis using VOSviewer software, the researchers identified and analyzed 97 relevant journal articles indexed in the Scopus database. The analysis revealed an upward trend in POGIL-related publications since 2016, with a significant concentration in the United States and in chemistry education journals. Key thematic clusters emerged around cognitive and affective learning domains such as engagement, academic achievement, reasoning, teamwork, and self-efficacy, indicating the predominance of student student-centered and active learning practices in POGIL implementations. However, the study found limited exploration of knowledge retention, misconceptions remediation, anxiety management, and the integration of digital learning tools in POGIL-based organic chemistry learning. The study concluded that POGIL holds strong potential for enhancing curriculum design and learning outcomes in chemistry education. It implied that future research should explore under-investigated areas, including the integration of appropriate technological innovations, to optimize the impact of POGIL on student learning in organic chemistry.